Nocardia pseudobrasiliensis Co-infection in SARS-CoV-2 Patients - Daniel Beau Stamos; Aldo Barajas-Ochoa; Jillian E. Raybould (Emerging Infectious Diseases, 2023)
During the SARS-CoV-2 pandemic, few cases of Nocardia spp. co-infection have been reported during or after a COVID-19 infection. Nocardia spp. are gram-positive aerobic actinomycetes that stain partially acid-fast, can infect immunocompromised patients, and may cause disseminated disease. We report the case of a 52-year-old immunocompromised man who had Nocardia pseudobrasiliensis pneumonia develop after a SARS-CoV-2 infection. We also summarize the literature for nocardiosis and SARS-CoV-2 co-infections. Nocardia spp. infection should remain a part of the differential diagnosis for pneumonia in immunocompromised hosts, regardless of other co-infections. Sulfonamide/carbapenem combinations are used as empiric therapy for nocardiosis; species identification and susceptibility testing are required to select the optimal treatment for each patient.